Response to BRAF and MEK Inhibitors in BRAF Thr599dup–Mutated Melanoma. (23rd March 2022) - Oberlé, Marion; Jamme, Philippe; Mansard, Sandrine; Machet, Laurent; Hervieu, Alice; Kramkimel, Nora; Greliak, Anna; Jarrousse, Anne Sophie; Derangère, Valentin; Dudoignon, David; Descarpentries, Clotilde; Mortier, Laurent
Abstract :